Vocabulary and Identification of Information: Difficulties and Challenges in Word Problems Solving - Unson, John Carlo (International Journal of Scientific Research and Management (IJSRM), 2021)
Word problems solving continues to be a problem for both students and teachers alike. As researches in word problem solving along reading comprehension are continuously undertaken, the problem remains timely and relevant as only few have shed light into the difficulties and challenges in word problem solving brought about by vocabulary and identification of information. This research intends to identify the areas of difficulties and challenges experienced by students and teachers in the senior high department in a top university in the Philippines, the University of the Cordilleras, which has a wide array of quality programs in the said department. Results obtained in this research may be used not only by students and teachers but also by authors, parents, aspiring teachers, aspiring school owners, or anyone who aspires for their personal development in Mathematics.